Fixed point and common fixed point results in ordered cone metric spaces - Choudhury Binayak S.; Metiya N. (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2012)
In this paper we establish some fixed point results for functions which satisfy certain weak contractive inequalities in partially ordered cone metric spaces. We have also given some illustrative examples. Our results are extension of some existing